2010
DOI: 10.1007/s12663-010-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Indigenous Stainless Steel Miniplates Used in Facial Fractures

Abstract: Aims and Objective The stainless steel (SS) implants are economical and easily available. Tissue reaction due corrosion of metallic plates and release of metal particles in surrounding soft tissues is the main reason put forward by advocates of removal of SS miniplates after period of fracture healing. The objectives of this study were to examine the surfaces changes and corrosion in relation to indigenously manufactured SS mini-plates, both due to intraoperative instrumentation and tissue reaction. The compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Roughness analysis of surface topographies has become a routine method in material design. [32][33][34] One of the reasons is the observation that cellular function strongly depends on the grade of roughness, 35,36 which has also been confirmed by in vivo experiments. 37,38 Roughness can be analyzed by profilometric techniques, which can be subdivided into mechanical contact and optical measurements.…”
Section: Reviewmentioning
confidence: 81%
“…Roughness analysis of surface topographies has become a routine method in material design. [32][33][34] One of the reasons is the observation that cellular function strongly depends on the grade of roughness, 35,36 which has also been confirmed by in vivo experiments. 37,38 Roughness can be analyzed by profilometric techniques, which can be subdivided into mechanical contact and optical measurements.…”
Section: Reviewmentioning
confidence: 81%
“…A large number of available fixators differ in shape, size and design features. The most common are metal plates and screws, which have the adequate stiffness and strength to provide stabile fixation of the bone fragments under cyclic functional load [1].…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel [1], titanium, and its alloys, zirconium alloys, tantalum are used for fixators manufacturing. According to modern concepts, these materials, should be biocompatible (from the chemical, physicomechanical and biological points of view) to avoid toxic and carcinogenic effect, as well as any kind of immune response [1]. However, studies of recent years have shown that none of the metal implants used in maxillofacial surgery, orthopedics or traumatology is completely inert.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation